Proactive Personality and Intent to Remain: Is Career Future a Moderator or Mediator? - Prabhu, Veena P. (Journal of Management Policy and Practice, 2018)
Individuals vary in their tendency to take action to control their environment. Proactive individuals actively create environmental change, while less proactive people take a more reactive approach toward their jobs. The extent to which individuals benefit from their own proactivity depends on the context. In the change context career future plays a vital role in affecting a proactive employee’s decision to remain with the organization. The purpose of the present study was to empirically test the mechanism by which proactive personality was related to intent to remain with the organization through career future. The results supported both the mediating and moderating role of career future in retaining proactive individuals. Implications for organizations and future research are discussed.